MODEL SIMULASI MEDIA MAKET DALAM PEMBELAJARAN MEMBACA DENAH SISWA SMPN 1 PUNGGELAN, BANJARNEGARA - Romelah Romelah (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2017)
The aim of this study is to improve the ability to read the roadmap. This study uses a two-cycle classroom action research, assigning students of SMPN 1 Punggelan Banjarnegara as the research subject. The implementation of this research refers to the spiral model from Kemmis and Taggart with four steps including: planning, implementation, observation, and reflection. Results of the research showed in cycle attainment in the average score was 73 and the mastery learning 41,38%. In the cycle II attainment was indicated by the average score 86,21 and the mastery learning  79.31%. Evidently, the use of mock media through simulation learning model can improve the ability to read plans.